Determining Factors Of Jump Service Volleyball In The Student Activity Unit Of Volleyball Muhammadiyah University Of Surakarta - Gatot Jariono; Haris Nugroho; Djoko Nugroho; Sae Dikdaya Nyatara; Tunjung Marganingrum; Dewi Setiawati (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2021)
The purpose of this study was to determine the determinants of serviceability in male athletes from the volleyball student activity unit at the University of Muhammadiyah using a factor analysis approach in terms of anthropometric and physical condition aspects. The population in this study were all male students of the UMS volleyball student activity unit, with a total of 40 people. The sampling technique used is purposive random sampling. data collection techniques with tests and measurements. The method used in this research is a quantitative research approach using a confirmatory analysis design. Data analysis using SPSS software version 22 and using Kaiser-Meyer-Olkin test and Bartlett's test.The results showed that anthropometric and physical condition factors that determine the sport's ability of male athletes in the student activity unit of the Muhammadiyah University of Surakarta consist of seven factors, namely height, arm length, leg muscle power, abdominal strength, arm muscle power, eye-hand coordination muscles. and flexibility of the stick. However, this research is only limited to the male sample group, furthermore, it is recommended to involve female samples and social environmental factors and are related to the increase in volleyball jump service.